The microtubule-associated protein MAP1B is involved in local stabilization of turning growth cones - Mack, Till G. A.; Köster, Michael; Pollerberg, G. Elizabeth (Molecular and cellular neuroscience, 2002)
For the development of the nervous system it is crucial that growth cones detect environmental information and react by altering their growth direction. The latter process is thought to depend on local stabilization of growth cone microtubules. We have obtained evidence of a role for the microtubule-associated protein MAP1B, in particular a mode 1 phosphoisoform of the molecule, P1-MAP1B, in this process. P1-MAP1B is tightly associated with the cytoskeleton and is present at highest concentrations in the distal axon and the growth cone of chick retinal ganglion cells. In growth cones turning at nonpermissive substrate borders, P1-MAP1B is restricted to regions which are stabilized. Unilateral neutralization of P1-MAP1B in one-half the growth cone by microscale chromophore-assisted laser inactivation changes growth cone motility, morphology, and growth direction. The results indicate a functional role for P1-MAP1B in local growth cone stabilization and thus growth cone steering.